Study the Need to Develop Principles for Using online Media in the Development of Mass Communication Work (Radio, Television, Print media) of the Department of Press, Culture and Tourism in Luang Prabang Province - SAIYVONGSAN, Chanthaphone; MEKTHANVANH, Vinath; PHEUAPHOM, Singthong; PHENGPHANYA, Phone; DUANGCHANH, Boy (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The purpose of this study is to investigate the need of principles development use in online media to develop the mass communication work (radio, television, print media) of the Department of Information, Culture and Tourism of Luang Prabang Province. It was conducting a quantitative research study by using questionnaire to collect data. And using the SPSS version 2022 to analize the data. The result found that the need of principles development use in online media to develop the mass communication work of the Department of Information, Culture and Tourism of Luang Prabang Province was in the high level especially the need to develop the aspect of refraining from responding with violence is in high need of development with a mean value of 4.38; SD = 0.68 and the need to develop the aspect of being careful in using your words and language correctly with a mean = 4.38; SD = 0.68, followed by the need to develop the aspect of being careful in using online social media with a mean = 4.21; SD = 1.11, the need to develop the aspect of the organization or department that is responsible for using online social media with a mean = 4.21; a SD =1.11. Next, the need to develop the aspect of using social media that is limited to the communication unit of using online social media with a mean = 4.31; SD = 0.54; the need to develop the aspect of avoiding using online social media with a mean = 4.14; SD = 1.03; the need to publicize on behalf of the organization is in high need the mean = 3.93; SD = 0.96; The need for organizational development is high with a mean = 3.79; SD 0.90, and the need for development in the use of social media images has a mean=3.69; SD = 0.89.